2019
DOI: 10.1108/idd-07-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Networked library access and services delivery for the blind and visually impaired university students: evidence from the UAE

Abstract: Purpose The study aims to discuss the special needs-centric information delivery as a new genre of the academic library services. It also sheds light on the assistive technology used to help blind or visually impaired (BVI) students to access the available digital contents and use online services conveniently. A particular emphasis placed on gaining some insights into BVIs’ perceptions towards the orientation and assistance offered by the access service librarians, as well as any experience in using assistive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, the lack of rights and opportunities to undergo and gain access to high recitation ratings like other members of society is still at an unsatisfactory stage (Khalil et al, 2022;Roslan et al, 2021). Students with disabilities convenience facilities, entry process, awareness stage for the provision of students with disabilities convenience between indicators of measuring the weakness of students with disabilities intimate education provision among service providers ranked high (Mahdzar et al, 2018;Al-Harrasi & Taha, 2019). So, this systematic literature review was conducted to analyze the gap in the study of indicators of students with disabilities-friendly higher education institutions among students with disabilities in Malaysia.…”
Section: Pwds Intimate High Recitation Issuementioning
confidence: 99%
“…However, the lack of rights and opportunities to undergo and gain access to high recitation ratings like other members of society is still at an unsatisfactory stage (Khalil et al, 2022;Roslan et al, 2021). Students with disabilities convenience facilities, entry process, awareness stage for the provision of students with disabilities convenience between indicators of measuring the weakness of students with disabilities intimate education provision among service providers ranked high (Mahdzar et al, 2018;Al-Harrasi & Taha, 2019). So, this systematic literature review was conducted to analyze the gap in the study of indicators of students with disabilities-friendly higher education institutions among students with disabilities in Malaysia.…”
Section: Pwds Intimate High Recitation Issuementioning
confidence: 99%
“…Al-Harrasi and Taha (2019) revealed that students with visual dysfunction complain about lack of support provided by libraries in accessing electronic content. Another study by Siamian et al (2014) found that libraries have not performed well in meeting the needs of visually impaired.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Several related studies were reviewed to understand the perception of visually impaired users relating to development of the information system. AI-Harrasi and Taha (2019) conducted a study on 35 blind and print disabled persons with the aim of understanding the use of resources in completing assignments. The study found that the university library failed to answer their needs for getting access to digital contents.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Therefore, they suggested that all stakeholders responsible for design and development of web content must work together and try to find solutions so that web content can be accessed by all. Al-Harrasi and Taha (2019) highlighted that students with visual dysfunction complain regarding lack of support provided by libraries in getting electronic content. Students also mentioned that online services provided by libraries are inadequate.…”
Section: Review Of Literaturementioning
confidence: 99%